Educação e organização curricular em turismo no ensino superior português - Salgado, Manuel (2010)
The analyzed thematic intends to interpret the educational and curricular reality in Tourism and suggests the convenient adaptations of the respectively formative system, at the national level. That action implies the introduction of some measures leading to the alteration of the particular formative policy, with the aim of creating a suitable model for the higher education system, supported by a network structure. Therefore, the object of investigation centers in the educational context of Tourism and the curricular organization in Portuguese higher education. The investigation systematizes the data from the study applied to the reality of that context, with the purpose to demonstrate the importance of this area after the implementation of the curricular and educational changes of the Bologna Process. In the sequence of this analysis, we can conclude that Tourism has been gradually recognized as a relevant Subject in the academic context, namely in Portugal.